Evaluation of the Possible Antioxidant Effects of Soybean and Nigella Sativa During Experimental Hepatocarcinogenesis by Nitrosamine Precursors. - A.A. El-Aaser (De Gruyter, 2007)
This study was designed to evaluate the possible antioxidant and antihepatocarcinogeniceffects of soybean (SB) and Nigella sativa (NS) in rats administered nitrosamineprecursors dibutylamine and sodium nitrate in the drinking water.Rats were randomly divided into four groups, each containing 48 animals. GroupI (control), group II (dibutylamine (DBA) + NaNO3), group III (DBA/NaNO3 + SBtreated) and group IV (DBA/NaNO3 + NS treated). Markers of oxidative stress [reducedglutathione (GSH) and nitric oxide (NO)] and the levels of HER-2/neu, bcl-2and p53 proteins were investigated in rats liver after 2, 4, 6, 8, 10 and 12 months.The data revealed an improvement in the status of oxidative stress represented asthe compensation of GSH levels after 2 and 4 months and reduction of NO levelsafter 2 months; a significant improvement in the levels of HER-2/neu protein after6 and 4 months in rats fed SB and NS, respectively. Although, the level of p53protein was ameliorated compared with the treated with nitrosamine precursor rats,it was maintained in a lower levels compared with the time matched points of thenormal controls until 12 months Both SB and NS improved the levels of bcl-2 after2 months in both groups. The data suggested that oral feeding of the diet containingSB and NS antagonized the oxidative stress effects induced by DBA/NaNO3.